2018
DOI: 10.1002/adma.201803703
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance of the Half Tin and Half Lead Perovskite Solar Cells by Suppression of the Bulk and Interfacial Charge Recombination

Abstract: In this article it is investigated how the hole extraction layer (HEL) influence the charge recombination and performance in half tin and half lead (FASn Pb I ) based solar cells (HPSCs). FASn Pb I film grown on PEDOT:PSS displays a large number of pin-holes and open grain boundaries, resulting in a high defect density and shunts in the perovskite film causing significant bulk and interfacial charge recombination in the HPSCs. By contrast, FASn Pb I films grown on PCP-Na, an anionic conjugated polymer, show co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 33 publications
3
99
0
Order By: Relevance
“…k) Reverse and forward J–V curves and l) EQE spectra of PSCs deposited on PEDOT:PSS and PCP‐Na HTLs. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: The Status Of Mixed Sn‐pb Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…k) Reverse and forward J–V curves and l) EQE spectra of PSCs deposited on PEDOT:PSS and PCP‐Na HTLs. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: The Status Of Mixed Sn‐pb Pscsmentioning
confidence: 99%
“…Shao et al reported that using PCP‐Na could improve the mixed Sn‐Pb film quality and the corresponding device performance . They claimed that FASn 0.5 Pb 0.5 I 3 perovskite films fabricated on PEDOT:PSS substrates have pinholes with poor coverage, which increases the risks of charge recombination and leakage current.…”
Section: The Status Of Mixed Sn‐pb Pscsmentioning
confidence: 99%
“…c) Schematic illustration comparing charge recombination (depicted with black arrow) processes in devices based on PEDOT:PSS and PCP‐Na hole extraction layers (HEL). Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Charge‐transporting Layers In Sn Halide Pscsmentioning
confidence: 99%
“…Many efforts have been devoted to improving the PCE of low‐bandgap mixed Pb–Sn PSCs . However, it often exhibits a larger open‐circuit voltage ( V oc ) loss, and therefore, its efficiency is far behind that of pure Pb‐based PSCs with a medium bandgap.…”
mentioning
confidence: 99%